Strategi Inovatif untuk Meningkatkan Minat Siswa dalam Pembelajaran Teori Musik Pada Pendidikan Dasar - Andriani; Yusna; Achmad Mieka Husaeini Pinem; Yamonaha Halaw; Anita Satriani (putrapublisher.org, 2023)
This research aims to find and apply new methods to increase students' interest in learning music theory. This is because students' interest in music theory has decreased. This research uses a qualitative approach with a literature review type of research. Data sources come from research results, books and websites that are relevant to the research. The data analysis used is content analysis. The research results show that the application of innovative strategies increases students' interest in learning music theory. Strategies that combine interactive and contextual elements have the greatest influence in increasing students' interest in music theory. This study provides music educators with important insight into the importance of change and innovation in teaching. Recommendations for educational practice and future research emphasize the need for approaches that better suit the needs and desires of today's students. These results add to the music education literature by demonstrating a useful method for addressing the problem of teaching music theory in modern schools.